Penerapan Hukum dalam Pemutusan Hubungan Kerja dan Kebijakan Bank Terhadap Debitur yang Terdampak Pandemi Covid-19 - Taun Taun; Ananda Nugraha (Batulis Civil Law Review, 2020)
Corona Virus Disease-19 (COVID-19) in Indonesia has a bad impact on the country's economy, banking, even the survival of the Community / Worker. The purpose of this study is to examine and analyze the legal consequences of employers who terminate the employment of PKWT workers who are affected by COVID-19 and the Bank's policy to set aside credit agreements for debtors affected by the termination of employment. This study uses a normative juridical research method with a statute approach and a case approach. The results show that the government's efforts to maintain public safety and maintain economic stability, in the spread of COVID-19, can affect the performance and capacity of micro, small and medium business debtors, thus potentially disrupting banking performance and financial system stability which can affect economic growth. Therefore, to encourage optimization of the banking intermediation function, maintain financial system stability, and support economic growth, an economic stimulus policy is needed as a counter cylical effect of the spread of COVID-19.